Cytotoxic and genotoxic effects of methanolic crude extracts from selected marine sponges collected from Terengganu Island on Acanthamoeba SPP - Ida Muryany Md Yasin (Fakulti Sains dan Teknologi, 2011)
Acanthamoeba is a free-living amoeba but pathogenic to humans, causing a potentially blinding infection of the cornea(keratitis). Keratitis is an important public health problem developing country. Therefore, research on new drugs for the treatment of this infection is still constitutes an important therapeutic demand. The objective of this study were determined the cytotoxic and genotoxic effects of crude extracts of sponges from Aaptos sp., Xestospongia sp. and Halicondria sp. collected from Kapas, Perhentian and Redang Islands, Terengganu on trophozoites of two clinical isolates namely Acanthamoeba castellanii (IMR isolate) and Acanthamoeba sp. (HKL isolate) and one free-living amoeba, Acanthamoeba polyphaga strain 1501/3A (but potential of being pathogenic).